Length-Weight Relationship and Condition Factors of Sarotherodon galilaeus (Linnaeus, 1758) from Nguru-Gashua Wetlands, Northeast Nigeria. - Ashley-Dejo Samuel Segun; Idi-Ogede Musa Abubakar; Mohammed Sabo; Musa Alhaji Musa; Ogah Samuel Ijabo (Jurnal Perikanan Universitas Gadjah Mada, 2023)
This study examined the length-weight relation and condition factor of Sarotherodon galilaeus (Linnaeus, 1758) from Nguru-Gashua wetlands, Northeast, Nigeria. A total of 375 specimens were purchased from local fishermen at the designated landing sites for six months. Results of morphometric characteristics showed that the body weight of male S. galilaeus ranged from 127-770 g (601.7±28.01) and females ranged from 272 – 704 g (711.3±38.12). Meristic features show that spinous anal fin rays were constant in both sexes while soft dorsal fin rays, pectoral fin rays, soft anal fin rays and spinous dorsal fin rays had the same range for both sexes. The sex ratio (1:2.18) observed in this study tends to favour male species but contrasts with the general assumption of a sex ratio of 1:1. Mean coefficient of determination was 0.89±0.07 and 0.87±0.07 for male and female S. galilaeus respectively indicating that length-weight relationship model is very reliable. This implies that the change in weight of the sampled fish was caused by 88.52% and 86.68% change in length of male and female S. galilaeus respectively.  It was further revealed that both sexes (b = 2.86±0.18 and 2.88±0.35) had negative allometric growth patterns. The wetland's environmental conditions were within a tolerable range for cichlids.